EVALUATION OF DRUG PRESCRIPTIONS IN A HOSPITAL EMERGENCY DEPARTMENT - Costa, Laiza Carvalho; Oliveira, Ana Paula de Freitas; Pires, Patricia da Silva; Cunha, Juliana Xavier Pinheiro da; Nunes, Emanuelle Caires Dias Araújo; Jesus, Jaqueline Santos de (Cogitare Enfermagem, 2023)
Objective: To evaluate the adherence of medical prescriptions to patient safety recommendations using the Medication Prescription Safety Checklist. Method: This is an observational, cross-sectional study carried out between May and June 2022, with 341 medical prescriptions for medicines in a hospital emergency room in the interior of Bahia - Brazil, whose data were analyzed through descriptive analysis. Results: 80% to 89% of the prescriptions adhered to the safety recommendations; the item with the highest adherence was identification of the date of the prescription, and the lowest adherence was having drugs with similar names identified in upper case or bold. Around 18.63% (n=514) of the drugs prescribed are on the list of potentially dangerous drugs for hospital use. Conclusion: The evaluation of medical prescriptions for medicines highlighted existing barriers in clinical practice, which makes it possible to develop more effective mechanisms to promote patient safety.